The prospects of food sovereignty in the former Yugoslav republics - Dokmanović, Mirjana (Teorija in praksa, 2021)
The neoliberal approach taken to the transition from socialism to capitalism in the six former Yugoslav republics has revealed its weaknesses in all spheres of economic activities, including food production. These countries have lost sovereignty with respect to regulating important national policy areas like food trade and production. Liberalisation of the food trade has adversely affected national economies by destroying many small-scale farmers and food producers. Corporate supermarkets have been taking over an ever bigger slice of the retail pie. Social movements are calling for direct democratic control over resources and food production to be regained. The article examines the prospects of these countries to overcome the increasing food insecurity by introducing food sovereignty
Keywords: bivše jugoslovanske republike; ekonomska demokracija; Food; Hrana; Liberalism; liberalizacija; liberalizacija prehranskega trga; Liberalizem; pravica do hrane; prehranska suverenost; prehranska varnost; Sovereignty; Suverenost; varnost